Language, voice and literature: expression of African spiritual experience in Zimbabwe’s Chimurenga war narratives - Viriri, Advice; Tembo, Charles (2016)
The thrust of this article is to give a critical literary synthesis of the immense contribution made by religion during Zimbabwe’s political struggle, as depicted in a selected body of Zimbabwean Chimurenga war narratives. It further posits that African spiritual religion played an integral role as a weapon to strengthen the indigenous people’s resistance to the injustices of racial discrimination during the liberation struggle. The indigenous people were spiritually guided as they fought a bitter war against ‘the alien invader who had expropriated their land, demeaned their culture and enslaved their bodies’ (Jones 1996, p. 50). The chosen war artists, through their common interest in, and common concern for, the preservation of fundamental human rights and values, point at the crucial role that African spiritual religion played - particularly in all the radical liberation war processes of socio-political change. Mbiti (1975) asserts that ‘Africans are notoriously religious’. African spirituality, as the article will show, managed to resolve the magnitude or intensity of contradictions within and between liberation movements, and against the enemy. In interpreting the lives of African people, the article will not sidestep comparisons that can manifest ideological overlaps, contradictions and crossovers among African religions and cultures. This reflection on African spirituality is evidence that Africans do not abandon their traditions, as is shown by their closeness to their religion that is similar to what a snail is to its shell: ‘Even in a foreign habitat, a snail never leaves its shell behind’ (lyasere 1975, p. 107). Contemporary voices of the black and African Diaspora, whose language reflects the experiences of African people across the continent, are pivotal to the liberation of the masses from colonial bondage. African religion invigorated and revitalised the masses’ energies, by richly inspiring the liberation struggle. The researchers’ theoretical protocols, with niches in African literary discourse, will include postcolonial theories.